2014
DOI: 10.5511/plantbiotechnology.14.0403a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrate concentration in nutrient solution on hemagglutinin content of Nicotiana benthamiana leaves in a viral vector-mediated transient gene expression system

Abstract: Viral vector-mediated transient expression enables rapid biopharmaceutical protein production using whole plants. In recent years, plant growth conditions have received close attention as factors influencing the content of recombinant protein. In particular, because nitrogen is an important resource used in protein synthesis, nitrogen supplied to the root zone may influence accumulation of recombinant proteins. We tested whether fertilization of Nicotiana benthamiana with high-nitrate nutrient solution during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Genetic (e.g., promoter selection and codon optimization), epigenetic (e.g., posttranscriptional gene silencing suppressor) and environmental (e.g., temperature) factors, as well as factors controlling protein stability (physiochemical/biochemical characteristics and the subcellular localizations of recombinant proteins) are the factors (Twyman et al, 2013). Additionally, our recent studies revealed that cultivation conditions, such as the composition of the nutrient solution supplied during plant growth before infiltration with Agrobacterium (agroinfiltration) and desiccation immediately after agroinfiltration, have significant impacts on the recombinant protein content (Fujiuchi et al, 2014(Fujiuchi et al, , 2016b. However, other factors may affect the yield-related quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic (e.g., promoter selection and codon optimization), epigenetic (e.g., posttranscriptional gene silencing suppressor) and environmental (e.g., temperature) factors, as well as factors controlling protein stability (physiochemical/biochemical characteristics and the subcellular localizations of recombinant proteins) are the factors (Twyman et al, 2013). Additionally, our recent studies revealed that cultivation conditions, such as the composition of the nutrient solution supplied during plant growth before infiltration with Agrobacterium (agroinfiltration) and desiccation immediately after agroinfiltration, have significant impacts on the recombinant protein content (Fujiuchi et al, 2014(Fujiuchi et al, , 2016b. However, other factors may affect the yield-related quantities.…”
Section: Introductionmentioning
confidence: 99%
“…Transient expression in N. benthamiana leaves was performed using transformed A. tumefaciens originating from strain GV3101::pMP90. The bacteria were transformed with a plasmid vector, pNM216 (Fujiuchi et al, ; Matsuda et al, ), derived from pICH26212 (magnICON; Icon Genetics, Halle/Saale, Germany). The T‐DNA present on pNM216 contains cDNA encoding a HA ectodomain derived from influenza A virus strain A/California/07/2009 modified to contain an N‐terminal secretory signal peptide and a C‐terminal endoplasmic reticulum‐retention signal peptide; it also contains cDNAs encoding tobamovirus‐derived RNA‐dependent RNA polymerase and movement protein.…”
Section: Methodsmentioning
confidence: 99%
“…Before agroinfiltration, 9th and 10th (in Expt I) or 8th and 9th (in Expt II) fully expanded leaves were detached from 35‐day‐old plants. Sixteen (in Expt I) or 28 (in Expt II) detached leaves were submerged in 2.3 L Agrobacterium suspension and vacuum‐infiltrated with the suspension as described in previous studies (Fujiuchi et al, ; Matsuda et al, ). Immediately after agroinfiltration, the detached leaves were removed from the suspension and wiped to eliminate any suspension remaining on the leaf surface.…”
Section: Methodsmentioning
confidence: 99%
“…Plant culture for transient expression is usually divided into two stages, the pre-inoculation and post-inoculation processes, which require different optimal environments. Cultivation conditions, such as the nutrient composition of the culture medium before agro-infiltration [55] and dehydration of plant material after agro-infiltration [70], are key factors. Changing environmental conditions at appropriate times during each stage may be required to obtain a high yield [56]; a high-nitrate nutrient solution during the pre-inoculation state results in high recombinant protein content [55].…”
Section: Transient Expression Systemsmentioning
confidence: 99%
“…Cultivation conditions, such as the nutrient composition of the culture medium before agro-infiltration [55] and dehydration of plant material after agro-infiltration [70], are key factors. Changing environmental conditions at appropriate times during each stage may be required to obtain a high yield [56]; a high-nitrate nutrient solution during the pre-inoculation state results in high recombinant protein content [55]. Very recently, interest in the surrounding environment has extended beyond research into the plant itself [57,58,71].…”
Section: Transient Expression Systemsmentioning
confidence: 99%